A survey of point insertion techniques in bidimensional Delaunay Triangulations - de Oliveira, Sanderson L. G. (INFOCOMP Journal of Computer Science, 2011)
Triangulations are geometric discretizations essential in many scientific applications, such as engineering simulations, visualizations, and geographic information systems. The preferred shape of a triangle depends on the applications. Theoretical and experimental analysis of numerical methods that are used in conjunction with triangulations suggest that triangles with no large angles and/or small angles serve well in most applications. This paper is a brief review of a point insertion in 2D Delaunay Triangulations. Important works on the insertion of vertices in Delaunay Triangulations are described as a start point for one who needs to build a quality mesh using adaptive triangular-mesh refinement.